De la subordinación a la hegemonía. Sobre la legitimación epistemológica de las matemáticas en la filosofía natural en el siglo XVII. (2013)
This article analyzes the epistemological legitimation of mathematics in natural philosophy in the seventeenth century. In the Renaissance it was claimed that mathematics does not meet the Aristotelian criteria of scientificity; and that it did not explain the efficient and final causes. So; its critics; inspired by the Aristotelian tradition; rejected the first attempts to mathematize natural philosophy. The epistemological conditions involved in the debate are examined on the scientific nature of mathematics and its relevance to natural philosophy. A historiographical tour of the mathematization of nature is made to provide new weighing elements with respect to a historically and philosophically more conceptual characterization of the emergence of modern science